Qurʾān Quotations Preserved on Papyrus Documents, 7th-10th Centuries - Kaplony, Andreas,; Marx, Michael, (Documenta Coranica, 2018)
Qurʾān Quotations Preserved on Papyrus Documents, 7th-10th Centuries is the first book on the Qurʾān's Sitz im Leben , id est on how the Qurʾān was quoted in Arabic original letters, legal deeds, and amulets. Qurʾān Quotations also serves as an in-depth exploration of the radiocarbon dating of documents and Qurʾānic manuscripts. Contributors: Ursula Bsees; Tobias J. Jocham; Andreas Kaplony; Michael Josef Marx, Daniel Potthast; Leonora Sonego; Eva Mira Youssef-Grob.